2013
DOI: 10.1089/jpm.2013.0173
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the Administration of Continuous Palliative Sedation: A Systematic Review

Abstract: Given the variation in study designs and the limitations of the included studies, the outcomes should be interpreted carefully. Further research is needed, particularly regarding factors that can be influenced and that may alter the course of a patient's symptoms and the patient's eventual need for palliative sedation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 30 publications
2
21
0
Order By: Relevance
“…37 Foley et al showed that a higher degree of palliative care specialization and sedation experience correlates with a physician's conviction that continuous deep sedation is not life shortening. 37 In line with previous studies, 4,12,35 we found a higher probability of receiving continuous deep sedation until death for patients younger than 65 and patients dying in hospital or specialized palliative care. However, only one in ten sedated patients died within specialized palliative care but at least one in three in nursing home and one in two in hospital, outside specialized palliative care units.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…37 Foley et al showed that a higher degree of palliative care specialization and sedation experience correlates with a physician's conviction that continuous deep sedation is not life shortening. 37 In line with previous studies, 4,12,35 we found a higher probability of receiving continuous deep sedation until death for patients younger than 65 and patients dying in hospital or specialized palliative care. However, only one in ten sedated patients died within specialized palliative care but at least one in three in nursing home and one in two in hospital, outside specialized palliative care units.…”
Section: Discussionsupporting
confidence: 91%
“…These findings are consistent with Dutch results pointing out that the use of opioids at admission to a specialized palliative care setting increased the probability of receiving continuous deep sedation. 35 The increasing trend of MELDs in Switzerland is in line with international findings, 8 except for the Netherlands showing a decrease of forgoing life-prolonging treatment decisions (20.2% in 2001; 18.2% in 2010). 10,15 The high proportional increase of forgoing life-prolonging treatment decisions combined with intensified alleviation of symptoms between 2001 and 2013 and the fact that patients continuously deeply sedated until death were most prevalent among those patients, might partly explain the fourfold increase of sedation practice.…”
Section: Discussionsupporting
confidence: 76%
“…refractory state (Bruce & Boston, 2011;Swart et al, 2014). The frequency of palliative sedation therapy for dying patients varies from 5%-52%, according to different sources (Bruinsma, Rietjens, Seymour, Anquinet & van der Heide, 2012;de Graeff & Dean, 2007), reflecting the wide range of the definition of palliative sedation, cultures, and practices (Maltoni, Scarpi & Nanni, 2014;Rosengarten, Lamed, Zisling, Feigin, & Jacobs, 2009;van Deijck, Hasselaar, Verhagen, Vissers, & Koopmans, 2013). Many of the patients who receive palliative sedation are patients with cancer (van Deijck et al, 2013).…”
mentioning
confidence: 99%
“…However, study results have suggested that implementing palliative sedation is more often linked to the attitudes and beliefs of physicians and to organizational settings than to the clinical needs of patients. 44 Other studies found a correlation between palliative sedation and higher doses of opioids used prior to implementing palliative sedation as well as between palliative sedation and younger patient age. 33,45,46…”
Section: Symptoms and Refractorinessmentioning
confidence: 97%
“…5,8,27 Some authors have focused on the search for early determinants for continuous palliative sedation so that patients at risk can be identified in a timely manner and their symptoms managed by other strategies. 33,[44][45][46] Information on determinants that more frequently lead to use of palliative sedation could also be used to assess the need for advanced care planning. However, study results have suggested that implementing palliative sedation is more often linked to the attitudes and beliefs of physicians and to organizational settings than to the clinical needs of patients.…”
Section: Symptoms and Refractorinessmentioning
confidence: 99%